PENGARUH IKLAN DI TELEVISI, KUALITAS PRODUK DAN HARGA TERHADAP CITRA MEREK SERTA IMPLIKASINYA PADA MINAT PEMBELIAN (Survei Pada Calon Konsumen Susu SGM Di Kota Malang) - Evi Suwarni; Suharyono Suharyono; Srikandi Kumadji (FIA UB, 2017)
This study aims to analyze and explain the Influence of Advertising on Television, Product Quality and Price toward Brand Image and Its Implication on Purchase Intention. This research was conducted using a survey method of potential consumers of milk SGM in Malang, with a total sample of 102 respondents. The analytical tool used is Path Analysis. The results showed that (1) Advertising on Television have significant effect toward brand image, (2) Product Quality have significant effect toward Brand Image, (3) Price have significant effect toward brand image, (4) Advertising on Television significant effect toward Purchase Intention, ( 5) Product Quality have significant effect toward Purchase Intention, (6) Price do not have significant effect toward Purchase Intention, (7) Brand Image have significant effect toward Purchase Intention. The three findings of this study as follows: (1) Advertising on Television have significant influence both directly and indirectly to the Purchase Intention through brand image, (2) Product Quality have significant influence both directly and indirectly toward Purchase Intention through Brand Image, (3) Price directly effect does not have significant toward Purchase Intention, but indirectly Price through of Brand Image have significantly influence toward Purchasing IntentionKeywords: Advertising on television, Product Quality, Price, Brand Image and Purchase IntentionABSTRAKPenelitian ini bertujuan untuk menganalisis dan menjelaskan pengaruh Iklan di Televisi, Kualitas Produk dan Harga terhadap Citra Merek serta Implikasinya pada Minat Pembelian. Penelitian ini dilakukan dengan menggunakan metode survei pada calon konsumen susu SGM di Kota Malang dengan jumlah sampel sebanyak 102 orang responden. Alat analisis yang digunakan adalah analisis jalur (Path Analysis). Hasil penelitian menunjukkan bahwa (1) Iklan di Televisi berpengaruh signifikan terhadap Citra Merek, (2) Kualitas Produk berpengaruh signifikan terhadap Citra Merek, (3) Harga berpengaruh signifikan terhadap Citra Merek, (4) Iklan di Televisi berpengaruh signifikan terhadap Minat Pembelian, (5) Kualitas Produk berpengaruh signifikan terhadap Minat Pembelian, (6) Harga berpengaruh tidak signifikan terhadap Minat pembelian, (7) Citra Merek berpengaruh signifikan terhadap Minat Pembelian. Keywords: Advertising on television, Product Quality, Price, Brand Image and Purchase Intention